THE EFFECT OF VIRTUAL THERAPY ON ANXIETY DISORDERS IN ADOLESCENTS: Case Study of Adolescents in Malang City - Aziz, Firman; Putra, Sudarmadi; Trianita, Desi (PT Altin Riset Publishing, 2023)
Objective study This is For The influence of virtual therapy on anxiety disorders in adolescents . Method used in study This is method study qualitative as for type research used studies case, usage studies case because researcher can understand in a way deep context, process, and complexity moderate phenomenon studied while the research location was Malang City . Results study this explain that virtual therapy has an effect in reducing the level of anxiety among teenagers in Malang City. Virtual therapy allows teens to remain in a space they consider safe, such as their bedroom, which can increase their openness and comfort in undergoing the therapeutic process. The results of these field findings provide information that reducing the level of anxiety among teenagers in Malang City requires collaboration between various parties, including educational institutions, government and society.